WHAT FACTORS INFLUENCE WHETHER 1 OR 2 UNITS OF BLOOD ARE USED WHEN INITIATING TRANSFUSION IN A STABLE, NON-BLEEDING POSTPARTUM MATERNITY PATIENT?. (February 2015) - Mayson, Eleni; Ford, Jane
Abstract : Background: Most obstetric blood transfusions occur in the setting of postpartum haemorrhage (PPH), however blood is limited, not risk-free and some women can be safely managed without a blood transfusion. There is variation in obstetric transfusion rates in NSW. Aim: To identify the factors influencing an obstetrician's decision to use 1 or 2 units of blood when initiating transfusion in a stable, non-bleeding postpartum maternity patient. Methods: A qualitative research study using semi-structured interview was conducted. Nine maternity units were chosen to cover a range of clinical settings and obstetric transfusion rates. Interviews were conducted with the key decision-makers in the maternity blood transfusion process. Interviews were transcribed, coded, and NVivo qualitative software was used to develop themes. Results: 126 interviews were conducted: 61 clinician interviews were coded in detail and the rest provided contextual data. Clinician-based factors such as perceived pros and cons, education, tolerance of maternal anaemia and personal prescribing practice influenced decision-making. External factors such as blood availability, blood product regulation, and the woman's views were also important. Conclusion: The decision to transfuse with 1 or 2 units of blood is complex and multifactorial. The decision to use 1 or 2 units does not reliably predict the hospital's overall obstetric transfusion rate.